2021
DOI: 10.1007/s10592-021-01332-7
|View full text |Cite
|
Sign up to set email alerts
|

Moving far, staying close: red fox dispersal patterns revealed by SNP genotyping

Abstract: The genetic structure of a population can provide important insights into animal movements at varying geographical scales. Individual and social behaviors, such as philopatry and dispersal, affect patterns of relatedness, age and sex structure, shaping the local genetic structure of populations. However, these fine scale patterns may not be detected within broader population genetic structure. Using SNP genotyping for pairwise relatedness estimates, we investigated the spatial and genetic structuring of 141 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…A more recent study by Walton et al [43], using fox samples in Sweden and which had been using a limited number of SNPs, reported an average estimated heterozygosity of 0.450. This value is higher than our observed value for H E of 0.302; indeed, the value reported by Walton et al [43] is closer to those values reported for microsatellite H E , which range from approximately 0.46 to 0.75 [20,44]. Therefore, estimated values of heterozygosity observed in this study may represent a loss of genetic diversity when compared to fox populations in the Northern Hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study by Walton et al [43], using fox samples in Sweden and which had been using a limited number of SNPs, reported an average estimated heterozygosity of 0.450. This value is higher than our observed value for H E of 0.302; indeed, the value reported by Walton et al [43] is closer to those values reported for microsatellite H E , which range from approximately 0.46 to 0.75 [20,44]. Therefore, estimated values of heterozygosity observed in this study may represent a loss of genetic diversity when compared to fox populations in the Northern Hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…In most mammal species, we observe female philopatry and male-biased dispersal [ 47 ], although female-biased dispersal is also observed in many species [ 48 ]. In red foxes, evidence from the current literature support both male-biased dispersal [ 49 ] and female-biased dispersal [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…During peak rodent phases, there was a trend, suggesting that social groups may be more common in remotely located dens. In Scandinavian red foxes, related females were more closely associated in space compared to males and individuals of opposite sex (Walton et al 2021 ), which is a likely consequence of male-biased dispersal and hence inbreeding avoidance. A similar pattern has also been observed in birds as Brouwer et al ( 2011 ) saw that female red-winged fairywren ( Malurus elegans ) moved further away if they were closely related to neighbouring males.…”
Section: Discussionmentioning
confidence: 99%